ANALISIS PEMBERIAN PINJAMAN, KREDIT BERMASALAH DAN SISA HASIL USAHA PADA KOPDIT CU MANDIRI TEBING TINGGI - Mezbah Theresyah Nababan; Jubi Jubi; Ady Inrawan; Astuti Astuti (JURNAL AKUNTANSI FINANCEIAL STIE SULTAN AGUNG, 2019)
The purpose of this research are: (1) To know out the granting of loans, non-performing loans and trade output remaind of  Mandiri Credit Union Tebing Tinggi. (2) To find out the factors that led to the granting of loans, bad debt and the rest of the results of the effort are experiencing fluctuations every year of  Mandiri Credit Union Tebing Tinggi. This research was used with qualitative descriptive analysis methods and inductive analysis. Data sources used in this research are primary and secondary data. Data collection is done by interview and documentation methods.Based on the results of the analysis of the research, it can be concluded that the fluctuating loan development tends to increase, the fluctuating development of non-performing loans tends to increase and the fluctuations in the remaining operating results tend to decrease.The results of the analysis suggest that the Mandiri Tebing Tinggi Credit Union Credit Union does not make it difficult for members to borrow and the procedures provided are not complicated, the loan interest is not too large so that members are not bored to make borrowing transactions, Mandiri Tebing Tinggi Credit Union Credit Union should approach the incoming members. into Non-Performing Loans, providing solutions to members who have difficulty paying their obligations, preferably the Mandiri Tebing Tinggi Credit Union Credit Union minimizes costs and reduces borrowing capital so that cooperatives are not burdened with loan interest costs and other operational costs. Keywords: The Granting Of Loans , Non-Performing Loans and Trade Output Remaind (SHU)